Extraction and characterization of chia (Salvia Hispanica l.) mucilage for application in food products - Borges, Viviane da Costa; Salas-Mellado, Myriam de Las Mercedes (VETOR - Revista de Ciências Exatas e Engenharias, 2020)
The present study aimed to carry out the extraction, characterization and comparison of oven-dried and freeze-dried chia mucilage, for use in food products. The chia seed mucilage was extracted and dried by two different methods: freeze-drying and conventional drying in an oven. The composition, microstructure and functional properties of the two mucilage were evaluated for application as food ingredients. The analyses held in the dried mucilage were % of yield, the determination of the functional properties: water holding capacity, oil retention capacity, emulsifying capacity and solubility, besides color and microscopy. The dried and freeze-dried chia mucilage showed similar proximal composition and distinct functional properties that confirm their use as ingredients in food products. The scanning electron microscopy analysis showed that the oven-dried mucilage has a structure similar to a film while the lyophilized mucilage has a fibrous and spongy structure.